PEDAGOGICAL FACTORS IMPROVING THE CREATIVE ASPECTS OF FUTURE MUSIC TEACHERS - Romanova, Sanobar Yerejepovna (SCIENCE and SOCIETY, 2026)
The article discusses the improvement of effective methods used in the process of training future music teachers in higher education based on modern pedagogical requirements, the importance of active and interactive methods in lessons, practical and creative activities, project activities, integrative education, and digital technologies in forming the professional and creative competence of future music teachers, and the systematic and targeted application of these meth- ods to train competitive, creative, and modern music teachers in the higher education system.
Keywords: pedagogue; skill; competence; creativity; education; singing; listening; music literacy; teacher's skills.